Lithography-free, high-density MoTe₂ nanoribbon arrays - Deng, Ya. (2022)
Two-dimensional (2D) materials have shown a range of extraordinary properties including superconductivity, topological states and ferroelectricity. Among them, 2D arrays with emerging properties have drawn intense interest due to their great potentials in implementing high-density electric devices and advanced integrated circuits. The controllable synthesis of large arrays of 2D elements offers the key advance but remains unsolved. Here we report a one-step chemical vapor deposition (CVD) synthesis strategy for achieving single-crystalline MoTe2 nanoribbon arrays directly on normal SiO2/Si substrate, requiring neither the special stepped substrate nor the post-processing. The lithography-free synthesized ribbons are found to be well-aligned with a density ten times higher than that reported in MoS2. Further scanning transmission electron microscopy (STEM) and first-principles calculation results reveal a crystal-structure boosted solid–liquid-vapor (SLV) self-etching mechanism. Our findings provide a convenient synthesis strategy to achieve high-density nanoarrays that serve as platforms for integrated nanoscale electric devices.